Novel solutions for closed-loop reverse electrodialysis: Thermodynamic characterisation and perspective analysis. (1st January 2019) - Giacalone, F.; Olkis, C.; Santori, G.; Cipollina, A.; Brandani, S.; Micale, G.
Abstract: Closed-loop Reverse Electrodialysis is a novel technology to directly convert low-grade heat into electricity. It consists of a reverse electrodialysis (RED) unit where electricity is produced exploiting the salinity gradient between two salt-water solutions, coupled with a regeneration unit where waste-heat is used to treat the solutions exiting from the RED unit and restore their initial composition. One of the most important advantages of closed-loop systems compared to the open systems is the possibility to select ad-hoc salt solutions to achieve high efficiencies. Therefore, the properties of the salt solutions are essential to assess the performance of the energy generation and solution regeneration processes. The aim of this study is to analyse the influence of thermodynamic properties of non-conventional salt solutions (i.e. other than NaCl-aqueous solutions) and their influence on the operation of the closed-loop RED. New data for caesium and potassium acetate salts, i.e. osmotic and activity coefficients in aqueous solutions, at temperature between 20 and 90 °C are reported as a function of molality. The data are correlated using Pitzer's model, which is then used to assess the theoretical performance of the whole closed-loop RED system considering both single and multi-stage regeneration units. Results indicate that KAc, CsAc and LiCl are the most promising salts among those screened. Highlights: Novel thermodynamics data for K and Cs acetate solutions are presented. New Pitzer's parameter determined from experimental data. The influence of solutions' osmotic & activity coefficients on RED Heat Engine is assessed. Optimal salt/solutions/operating conditions are identified for maximum efficiency of RED-HE.